PENDIDIKAN DI ERA OTONOMI DAERAH PASCA ORDE BARU - Junaidi Junaidi (Kuttab : Jurnal Ilmu Pendidikan Islam, 2020)
The education system in Indonesia has experienced many changes since the change in the decentralized political system. Legally, these changes have been legitimized with various applicable laws and regulations. The leading spirit of the decentralization of education is to provide more full opportunities for regional authorities to innovate and take advantage of local excellence in the delivery of instruction. However, in addition to the many positive things that were obtained from the decentralization of education, several unfavorable things happened. Therefore, it is necessary to further and more in-depth study of the effectiveness of the implementation of school with a decentralized pattern.